3(x-2)=0.4x-3+0.1x+4

Simple and best practice solution for 3(x-2)=0.4x-3+0.1x+4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(x-2)=0.4x-3+0.1x+4 equation:


Simplifying
3(x + -2) = 0.4x + -3 + 0.1x + 4

Reorder the terms:
3(-2 + x) = 0.4x + -3 + 0.1x + 4
(-2 * 3 + x * 3) = 0.4x + -3 + 0.1x + 4
(-6 + 3x) = 0.4x + -3 + 0.1x + 4

Reorder the terms:
-6 + 3x = -3 + 4 + 0.4x + 0.1x

Combine like terms: -3 + 4 = 1
-6 + 3x = 1 + 0.4x + 0.1x

Combine like terms: 0.4x + 0.1x = 0.5x
-6 + 3x = 1 + 0.5x

Solving
-6 + 3x = 1 + 0.5x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-0.5x' to each side of the equation.
-6 + 3x + -0.5x = 1 + 0.5x + -0.5x

Combine like terms: 3x + -0.5x = 2.5x
-6 + 2.5x = 1 + 0.5x + -0.5x

Combine like terms: 0.5x + -0.5x = 0.0
-6 + 2.5x = 1 + 0.0
-6 + 2.5x = 1

Add '6' to each side of the equation.
-6 + 6 + 2.5x = 1 + 6

Combine like terms: -6 + 6 = 0
0 + 2.5x = 1 + 6
2.5x = 1 + 6

Combine like terms: 1 + 6 = 7
2.5x = 7

Divide each side by '2.5'.
x = 2.8

Simplifying
x = 2.8

See similar equations:

| .10c+24.95=19.95+.20c | | 7+47z=14x^2 | | 20-4m=12 | | 29-6v=(-55) | | 3d+3=12-6d | | x+2(2)=16 | | -18x+12y=-18 | | 5x-6(4x-1)=8 | | 16=24-4t | | 4+x=-4+-1x | | 3(4d+1)-9d=6(-2m+5)-4 | | x-(2x+3)=-4 | | 2x^3+7x^2-7x-30=0 | | 2w+2(6w-6)= | | 5+3x=5x+7 | | 60=4(6r+3) | | Z-4.3=1.6 | | x+(3x+11)=3 | | (11x-1)+(5y-5)=180 | | -12x+8y=-12 | | -22x+9x= | | 8.3z=4.1z+10.2 | | 0.128-0.035v=0.072v+0.235 | | 6x-x=3x+30 | | 15=5d-5 | | 44-(-b)=76 | | 5x-3+7-8x=19 | | (T)=t^2+100t | | 5z+2=3iz+4i | | wx+b=yforx | | 6c-8=4c | | x+2=-6+72 |

Equations solver categories